2014
DOI: 10.3136/fstr.20.891
|View full text |Cite
|
Sign up to set email alerts
|

Screening Study on Antioxidant Activity of Plants Grown Wildly in Mongolia

Abstract: In this study, 50% ethanol extract prepared from dry leaves of eight plants grown wildly in Mongolia were characterized for DPPH radical scavenging activity, ABTS radical cation scavenging activity, superoxide anion scavenging activity, ferric reducing power, iron chelating ability, and content of total phenol, flavonoid, and flavanol in order to find good sources of natural antioxidant from plant kingdom. Correlation coefficients between antioxidant parameters and contents of polyphenolic compounds were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Enkhtuya et al, investigated radical scavenging and reducing activities of different plants, and found that in DPPH, ABTS, and FRAP methods of analysis lingonberry leaves were more active than leaves of black currant, hawthorn, strawberry, and tall currant. Radical scavenging and reducing properties of lingonberry leaves were similar to that of seabuckthorn [ 16 ]. Vyas et al found significant differences of radical scavenging and reducing activities of lingonberry leaves within wild clones and cultivars, and distinguished V. vitis-idaea subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enkhtuya et al, investigated radical scavenging and reducing activities of different plants, and found that in DPPH, ABTS, and FRAP methods of analysis lingonberry leaves were more active than leaves of black currant, hawthorn, strawberry, and tall currant. Radical scavenging and reducing properties of lingonberry leaves were similar to that of seabuckthorn [ 16 ]. Vyas et al found significant differences of radical scavenging and reducing activities of lingonberry leaves within wild clones and cultivars, and distinguished V. vitis-idaea subsp.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that lingonberry leaves exhibit great ability to donate hydrogen atom or transfer single–electron. Concerning chelating activity, some researchers reported that lingonberry extracts showed weaker chelating activity than extracts from plants belonging to other families [ 16 , 17 ]. However, it is difficult to compare the antioxidant activity results obtained in the present study with the literature data, because of the differences in methods and expression of antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous results, the 50% ethanol extract of peony leaf showed remarkable scavenging activity against DPPH radicals, ABTS radical cations and superoxide anions, and exerted significant ferric reducing antioxidant power. The extract also contained a considerable amount of phenolics (Enkhtuya et al, 2014).…”
Section: Resultsmentioning
confidence: 98%
“…We previously reported a screening study on the antioxidant activity of leaves from eight plants growing wild in Mongolia (Enkhtuya et al, 2014). From the results, we found that peony leaf was the most effective candidate for further study.…”
Section: Introductionmentioning
confidence: 94%
“…Among the selected plant leaves, V.vitis-idaeae, P.anomala, R.acicularis, and H.rhamnoides had significant antioxidant potential and were rich in polyphenolics. In particular, P.anomala leaf showed remarkable scavenging activity against DPPH radicals, ABTS radical cations and superoxide anions, and exerted significant ferric reducing antioxidant power [1]. Afterwards, we identified three main constituents in P.anomala leaf, namely methyl gallate, pentagalloylglucose, and tellimoside, which showed potent DPPH radical scavenging activity [2].…”
Section: Introductionmentioning
confidence: 99%